2010
DOI: 10.1007/s10641-010-9636-7
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive biology of Bigeye Tuna, Thunnus obesus, (Scombridae) in the eastern and central tropical Pacific Ocean

Abstract: Understanding the reproductive potential of any species is of great importance for resource assessment and management. We studied the reproductive biology of Bigeye Tuna, Thunnus obesus, based on 1283 samples taken from the Chinese longline vessels in the eastern and central Tropical Pacific Ocean during February through November 2006. The female-male ratio was 1.0 : 1.5 and males were predominant in all length classes except for the length class of 166-170 cm (fork length). Males dominated in sizes larger tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…a). The proportion of characteristic behavior increased with fish size, being dominant for 65–70 cm FL (age 1, based on growth curve by Zhu et al ., ) (59%), which coincides with the size at which the mean duration of this behavior increases (Fig. b).…”
Section: Resultssupporting
confidence: 73%
See 3 more Smart Citations
“…a). The proportion of characteristic behavior increased with fish size, being dominant for 65–70 cm FL (age 1, based on growth curve by Zhu et al ., ) (59%), which coincides with the size at which the mean duration of this behavior increases (Fig. b).…”
Section: Resultssupporting
confidence: 73%
“…The length of the fish at recapture was used to calculate the change in length, assuming a constant growth rate because growth rate for <100 cm FL fish seems almost constant based on the growth curve by Zhu et al . () and seasonality of growth cannot be expressed based on that study. If length at recapture was not available, a length was estimated based on the length at release, and with comparison of other fish in the present study of similar size, in the same season with a similar number of days at liberty.…”
Section: Methodsmentioning
confidence: 80%
See 2 more Smart Citations
“…Studies with Bigeye tuna and Yellowfin tuna in the Pacific Ocean reported significant differences between the sexes, and males once again predominated. This suggests that the distinction between the number of males and females may also be related to the selectivity of the several fishing gear types used to catch these individuals in different regions of the ocean (Schaeffer 2001, Zhu et al 2010. Polygamy behavior during spawning is another hypothesis to explain the male biased sex ratio.…”
Section: Discussionmentioning
confidence: 99%